One-stage Assay for Hageman Factor (Factor XII). Further Studies on the Role of Hageman Factor in Blood Coagulation - Haanen, C; Schoenmakers, John G. G (Thrombosis and Haemostasis, 1963)
A one stage assay for Hageman Factor (HF) activity is described. Maximal standardization was achieved by lyophilizing substrate plasma, cephalin suspension and standard reference plasma in small aliquots. A dilution curve was constructed, using a highly purified HF preparation. The assay is not completely specific and is invalidated by the presence of activated Factor IX and XI. So all materials to be tested were first adsorbed on Al(OH)3-gel to exclude Factor IX and possibly most of Factor XI.Purified activated HF still possesses a high affinity for glass surfaces, thus activation may not alter the molecule at the side of affinity for the glass surface. Moreover purified activated HF is still more active in the presence of glass thus in the adsorbed state. These observations support the idea that the so called activation of Hageman Factor is a reversible phenomenon, whereby the molecule unfolds and uncovers active groups as soon as it is adsorbed on a negatively charged surface.